Criminal Courts in the Kosciuszko Uprising (an outline) - Ewa Stawicka (Journal on European History of Law)
The document explores the establishment and functioning of criminal courts during the Kosciuszko Uprising, highlighting the innovative legal system and the procedural aspects adopted in the face of political turmoil. It delves into the challenges faced by these courts, the influence of political dynamics on justice, and the efforts to maintain law and order amidst the insurrection. The study also reflects on the broader implications of these legal practices in the context of European legal history.